Evaluation of Primigravida Pregnant Women Perceived Stress during Second Trimester of Pregnancy - Suhad Hassan Omran, Lujain Anwar Al-Khazraji (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate primigravida pregnant women’s perceived stress during the first trimester of pregnancy and to compare between these women relative their perceived stress and pregnancy trimesters, and to determine the relationship between these women’s perceived stress and their demographic characteristics of age, women’s education, women’s occupation, spouses’ education, spouses’ occupation, maternal medical history, and monthly income. Methodology: Time dimension study design, using a longitudinal “follow-up type” study was conducted in primary health care centers from the health care sectors at Al-Russafa and Al-Karkh Health Directorates in Baghdad City, for the period of October 15th 2020 through January 17th 2022, in order to evaluate Primigravida women’s perceived stress. The sample was Convenient, non-probability, sample of (300) primigravida pregnant woman who are recruited from (10) main, (10) sub and (10) family medicine primary health care centers, (150) woman at Al-Russafa and (150) woman at Al-Karkh in Baghdad City. All primigravida pregnant women, who have participated in the study, have signed consent form for their agreements for the participation in the study. The questionnaire was designed as an instrument for collecting data through the use of the Self-report questionnaire was constructed for the purpose of the study. The study instrument was constructed through review of relevant literature, the questionnaire which consisted of two main parts. The first part relates to the primigravida pregnant women socio-demographic characteristics (such as age, woman’s education, woman’s occupation, spouse’s education, spouse’s occupation, pregnancy woman’s medical history, monthly income) and the second part relates to the stressors that cause primigravida’s perceived stress. This part is comprised of (70) item that evaluate primigravida pregnant women’s perceived stress during pregnancy these items are distributed throughout (6) dimensions that include physical stressors (20) items, cognitive stressors (11) items, social stressors (16) items, emotional stressors (8) items, behavioral stressors (9) items and financial stressors (6) items. All items are measured on 3-level type Likert scale of never = 1, sometimes = 2 and always = 3. A pilot study was carried out for the period of November 4th through December 14th 2020 in order to determine the validity and reliability of the study instrument to (12) primigravida pregnant women. The reliability of the questionnaire was determined by using the Cronbach Alpha test, and the content validity of the questionnaire was determined throughout panel of (12) experts. The data were analyzed and described using the descriptive statistical data analysis approach of frequency, percentage, mean, standard deviation, mean of scores, total scores and ranges and inferential statistical data analysis approach of analysis of t-test, analysis of variance, multiple linear regression Results: The results of the study have indicated that the majority of the primigravida pregnant women have experienced high level of perceived stress during the second trimester of their pregnancy (90.3%). Also, the results of the study revealed that there is no relationship between perceived stress and socio-demographic characteristics. Conclusion: The study concluded that it confirms that primigravida pregnant women can develop perceived stress during the second trimester of pregnancy, the perceived stress can be elevated as far the pregnancy is emerging and progressing, primigravida pregnant women’s perceived stress is no influenced by the discrepancies in their demographic characteristics and their spouses’ demographic characteristics as well. Recommendations: The study recommended that the early detection and management of stress during pregnancy are important to deal with perceived stress among primigravida pregnant women, health education programs, targeting the reduction of stress during pregnancy, may help to reduce its potential adverse health effects on the mother and child, counselling service can be activated and motivated for the benefits of both the primigravida pregnant women and their families throughout the family-centered primary healthcare centers, Further research can be conducted on the same topic with respect to large sample size and wide-range scale of characteristics.